Analisis Numerik Perkerasan Sistem Pelat Terpaku Tiang Tunggal menggunakan Tiang Pipa Baja pada Tanah Lunak - Puri, Anas (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
All of the full-scale tests and numerical analysis of Nailed-slab System from previous researchers used massive reinforced concrete piles. This research will study the possibility of steel pipe pile as a replacement of massive reinforced concrete piles if there are available enough steel pipe piles. This research is aimed to study the behavior of single steel pipe pile Nailed-slab System on soft clay and the influence of pile length due to slab deflection and soil stresses. It was used the data from Puri (2015a) for a single massive reinforced concrete pile Nailed-slab. This massive reinforced concrete pile was replaced by a single steel pipe pile with similar and varied diameter which analyzed by the 2D finite element method. Results show that the steel pipe pile can be used as a “nail” at the Nailed-slab pavement system but by a larger dimension compared to the massive reinforced concrete pile. The maximum effective shear stress in soil did not reach undrained shear strength under a standard wheel load 40 kN. Generally, the soil was not failure.